Communication process in order to maintain mental health during the COVID-19 pandemic among indonesian students - Melly Maulin Purwanigwulan; Tine Agustin Wulandari (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This research conducted to analyze in depth about the communication process that started from the psychological (mental) symptoms that arise during the pandemic, communication partners, ideal communication approaches, and messages that conveyed in order to maintain mental health of students in Indonesia during the Covid-19. Through qualitative approach with case study method, this research is expected to provide a deeper understanding of the researched problem. Researchers paid attention and examined an issue of interest, and used a single case as an instrument to describe it in detail. Result of this research showed that students are very at risk for mental health disorders during the pandemic. Symptoms that they experienced are anxiety disorders, stress, burnout, depression, loneliness and relationship problems. Family and friends are the most appropriate communication partners during the pandemic. The pandemic creates a revolution momentum to restore the role of the family for children. Interpersonal communication is still considered as the most ideal approach. The majority communication messages are emotional, spiritual and motivational messages. As a result of this research, it is hoped that the government and universities will increase the awareness of students' mental health because of the lack of counseling related to mental health for students.